Dental Services Satisfaction and Perceived Quality in a School-Based Clinic in Cartagena, Colombia (2016)
Objective: to describe the level of quality and perception of satisfaction in attended users from a school-based dental clinic in Cartagena, Colombia. Methods: we performed a cross-sectional study in 277 patients. For data collection we applied a structured and self-administered survey asking for demographic, clinic attention topics and specific questions regarding quality and services satisfaction. Data analysis was performed through descriptive statistics with frequencies, proportions and 95% confidence intervals. Bivariate analysis was conducted using X2 tests to test independence between variables. Results: more than a half of the users were females and overall average age was 39 (SD: 12,48) years-old. 99,3% (95% CI: 98,2 - 100) of the subjects referred to be satisfied with the dental care and 97,8% (95% CI: 96,1-99,5) perceived a good quality. When relationship with demographic variables was tested, we didn’t find any statistical significant association between the variables. Conclusion: users perception about quality and global satisfaction in dental services is perceived satisfactorily. Nevertheless, these results do not suggest the presence such quality. It is important for the institution to perform users satisfaction follow-up because in some domains as human resources there is still evidence of unconformity.